Ends of the Earth : journeys to the Polar Regions in search of life, the cosmos, and our future - Shubin, Neil (Dutton, 2025)
"The bestselling author of Your Inner Fish takes readers on an epic adventure to the North and South Poles to uncover the secrets locked in the ice and profoundly shift our understanding of life, the cosmos, and our future on the planet. For three decades, renowned scientist Neil Shubin has made extraordinary discoveries by leading scientific expeditions to the sweeping ice landscapes of the Arctic and Antarctic. He's survived polar storms and faced the limits of human endurance to explore questions of how life survived and adapted, and what our future on a changing planet may hold. Scientific discoveries at Earth's polar regions have changed the way we see the world and these insights are becoming ever more urgent. These landscapes are the epicenter for rapid change to our planet, with ice retreating, animal species moving toward the equator or going extinct, Indigenous communities confronting dramatic environmental changes, and political battles heating up for newly accessible mineral and gas resources. In the end, what happens at the poles does not stay in the poles--events there in the coming years will affect all life and every nation on the planet. The book blends travel, science, and environmental writing to deepen our understanding of animal and plant life, the history of our ice ages, the age of dinosaurs, the history of Western exploration, and the clues meteorites preserved at the poles contain about the cosmos. Written with infectious enthusiasm and irresistible curiosity, Shubin shares lively adventure stories from the field to reveal just how far scientists will go to understand polar regions and to reveal the poles' impact on the rest of life on the planet"--